Determinants of adoption of HYV rice in West Bengal - Saha Anamitra (Kolkata K P Bagchi, 2004)
Estimation of a stochastic yield function using nonlinear regression technique showed that cultivation of rice involved significantly higher risk compared to traditional rice while inputs were largely risk neutral in both technologies. A switching regres
Keywords: Rice cultivation; West Bengal